State Authority and Public Trust in National Zakāh Management: Historical Lessons, Fiqh Discourse, and International Comparison - Yusuf Wibisono (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
The aspect of zakāh management or administration is not regulated extensively in Islamic law. Since the dawn of Islam, zakāh management has become the field of ijtihād based on mashlaḥah. And today, the practice of zakāh management in contemporary Muslim countries has been incarnating a wider area of experiment. In contemporary Indonesia, the Law Number 23 Year 2011 concerning Zakāh Management has been passed. This law, which become effective since 2016, caused upheaval within national Islamic philanthropy sector since it regulates national zakāh management currently dominated by civil society, based on “classical fiqh opinion” that only the state has authority to manage zakāh. This paper lift up an important conclusion that zakāh management entirely by the state is not be in effect unconditionally, but with many of qualifications. Moreover, the effectiveness of zakāh management by state relies heavily on the level of public trust against government, not by enforcement of the state. Zakāh management by the state is merely an instrument, not the goal itself. The ultimate objective that must be pursued is the delivery of zakāh to those who deserve it with optimum benefits.